Multifocal histiocytic sarcoma of the gastrointestinal tract - Shirley Sundersingh; Urmila Majhi; Ramakrishnan Ayloor Seshadhri; Gnana Sagar Tenali (Wolters Kluwer Medknow Publications, 2012)
We report a rare case of extranodal histiocytic sarcoma with multifocal gastrointestinal tract involvement, which has not been documented in the literature so far. A diagnosis of interdigitating dendritic cell/ histiocytic sarcoma was made on the preoperative gastric biopsy. Computed tomography scan revealed multifocal, circumferential gastrointestinal wall thickening involving the stomach and jejunal loops. Patient underwent distal gastrectomy with extended D1 dissection and proximal jejunal resection with gastrojejunostomy. Immunohistochemistry profile of both the gastric and jejunal tumors was similar to the preoperative gastric biopsy. The histiocytic origin of the tumor was confirmed by positive reaction of the tumor cells for CD 163. She received four cycles of CHOP chemotherapy, and is free of disease three years, following surgery.